Transformational Leadership: A Compound of Competencies - Mohan Venkata Ram, B.; Shishigu, Assegid Demissie (Prabandhan: Indian Journal of Management, 2011)
The purpose of this article is to highlight some of the ingredients or elements of transformational leadership that make up the compound of transformational leadership. Now, more than ever, in this dynamic and complex environment, transformational leadership is proved to be the appropriate leadership style that plays the key role in helping organizations cope with the challenges they face from expanding knowledge. This article addresses the question, what qualities or skills or magic make leaders transformational? All data are obtained from secondary sources. Various studies and literature are reviewed. The empirical research reveals that transformational leadership is compound of different skills, qualities and competencies. This article focuses on some of these elements such as, Credibility, Visionary, Empathy, etc.